2019
DOI: 10.1002/jbio.201800462
|View full text |Cite
|
Sign up to set email alerts
|

Potential of contrast agents to enhance in vivo confocal microscopy and optical coherence tomography in dermatology: A review

Abstract: Distinction between normal skin and pathology can be a diagnostic challenge. This systematic review summarizes how various contrast agents, either topically delivered or injected into the skin, affect distinction between skin disease and normal skin when imaged by optical coherence tomography (OCT) and confocal microscopy (CM). A systematic review of in vivo OCT and CM studies using exogenous contrast agents on healthy human skin or skin disease was performed. In total, nine CM studies and one OCT study were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Optical coherence tomography (OCT) is applied with great success in the eye as well as in inner organs through endoscopes [ 99 ]. Besides, confocal microscopy (CM) has been widely utilized in skin diseases, like melanoma and inflammatory, aiding not only an in vivo diagnosis of skin abnormalities but also choosing better therapies and following the patient’s response to treatment [ 62 ].…”
Section: The Molecular Imaging-based Multiscale Pathology Visualizationmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is applied with great success in the eye as well as in inner organs through endoscopes [ 99 ]. Besides, confocal microscopy (CM) has been widely utilized in skin diseases, like melanoma and inflammatory, aiding not only an in vivo diagnosis of skin abnormalities but also choosing better therapies and following the patient’s response to treatment [ 62 ].…”
Section: The Molecular Imaging-based Multiscale Pathology Visualizationmentioning
confidence: 99%
“…19,20 In non-invasive optical imaging, the gold microparticles have shown to act as hyper-reflective contrast agents. [21][22][23] providing insight about hair follicle characteristics and density. The use of microparticle encapsulation for drug-laden carrier systems has been gaining traction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that transfollicular delivery is a feasible pathway to distribute 120 nm gold microparticles to the pilosebaceous unit 19,20 . In non‐invasive optical imaging, the gold microparticles have shown to act as hyper‐reflective contrast agents 21–23 . providing insight about hair follicle characteristics and density.…”
Section: Introductionmentioning
confidence: 99%
“…However, this required topical application of aluminium chloride (AlCl) to optimise nuclear morphology brightening and BCC tumour-to-skin contrast (9). Misrepresented nuclear morphology and tissue necrosis could result depending on the concentration used (9,16). Moreover, they harbour risks for side effects (16).…”
Section: Introductionmentioning
confidence: 99%
“…Misrepresented nuclear morphology and tissue necrosis could result depending on the concentration used (9,16). Moreover, they harbour risks for side effects (16).…”
Section: Introductionmentioning
confidence: 99%